Role of heterojunction ZrTiO4/ZrTi2O6/TiO2 photocatalyst towards the degradation of paraquat dichloride and optimization study by Box–Behnken design - Badli, N. A. (Elsevier B.V., 2017)
This study revealed that the existence of heterojunction of ZrTiO4/ZrTi2O6/TiO2 in the photocatalyst system has significantly enhanced the photodegradation of paraquat dichloride with respect to the increment of it thermal stability as shown in the XRD and XPS analyses. Several parameters such as ZrO2/TiO2 ratios (10:90, 20:80 and 30:70) and catalyst dosage (0.1–0.4 g) have been studied to achieve the optimum degradation of paraquat dichloride. The kinetic study was determined by using various ZrO2/TiO2 ratios calcined at 750 °C and showed that the photodegradation of paraquat over ZrO2/TiO2 photocatalyst follows a pseudo first-order kinetic. The optimum condition was obtained using ZrO2/TiO2 (20:80), calcined at 750 °C and with 0.3 g catalyst dosage which gave 84.41% degradation after 240 min under UV irradiation, λUV = 365 nm. The N2 adsorption–desorption analysis shows the mixture of Type III and IV isotherms with hysteresis loop type H2(b). Meanwhile, the Box–Behnken design showed the optimum photodegradation of paraquat was obtained at the calcination temperature of 750 °C, with the ZrO2/TiO2 ratio of 20:80 and 0.3 g catalyst dosage which was 0.24% lower than our experimental verification result.